Effectiveness of Sodium Dodecyl Sulphate (SDS) and Hydrogen Peroxide (H2O2) in The Decellularization Process of Biological Tissues - Sukanto, Daud Yudhistira; Soebroto, Heroe (Journal of Neonatal Surgery, 2025)
Background: Tissue engineering requires an effective decellularization process that eliminates cellular components while preserving the extracellular matrix (ECM). Sodium Dodecyl Sulphate (SDS) and Hydrogen Peroxide (H₂O₂) are two common agents used in this process. Objective: To analyze the effectiveness of SDS and H₂O₂, both individually and in combination, in the decellularization of biological tissues. Methods: A narrative literature review was conducted using electronic databases (PubMed, ScienceDirect, Google Scholar) with keywords including "decellularization," "SDS," "hydrogen peroxide," "biological scaffold," and "tissue engineering." Eighteen articles published between 2010 and 2025 were selected based on inclusion and exclusion criteria. Results: SDS showed high efficacy in cellular removal but posed risks of ECM degradation, particularly at high concentrations or prolonged exposure. H₂O₂ was less effective in removing cells but preserved ECM structure better. The combination of SDS 0.5% and H₂O₂ 3% offered the most optimal results, yielding acellular scaffolds with well-preserved ECM and low residual toxicity. Conclusion: Combining SDS and H₂O₂ offers synergistic advantages in decellularization, achieving effective cell removal while maintaining ECM integrity. This approach is promising for future tissue engineering applications.